An integrated approach to the treatment of a patient with chronic tonsillitis. Clinical case - Khiyir T. Abdulkerimov; Ksenia I. Kartashova (Consilium Medicum)
Chronic tonsillitis (CT) is a common infectious-allergic disease leading to severe general somatic complications, including rheumatic damage of joints and heart, kidney disease. Currently in Russia there is an increase in the number of patients with CT. Therapy for CT in outpatient practice is often limited to only washing the lacunae of the palatine tonsils, without the use of local drugs. We observed a 35-year-old patient with a diagnosis of chronic tonsillitis and a history of the disease of more than 1.5 years. A combined method of therapy was chosen, including treatment with the Tonsillor apparatus using low-frequency ultrasound therapy and local use of Viroxinol for irrigation of the tonsils and mucous membrane. As a result of the complex treatment, pronounced positive dynamics and a decrease in the clinical symptoms of CT were achieved.